Needs and wants in mosque architecture: a study of traditional and modern mosques in West Java-Indonesia - Wirakusumah, Indri Astrina; Antariksa, Antariksa; Salura, Purnama (Linguistics and Culture Review, 2021)
Generally, the study on mosque architecture focuses partly on classifying mosque forms or exploring the historical, socio-cultural, and political meanings behind the architectural design of mosques. This study puts forward a new concept of an interesting relationship between the needs of Islamic ritual activities and the wants of certain traditions that underlie the diversity of mosque architectural forms in Indonesia. Therefore, the search for these two essential aspects of mosque architecture is important to position the diversity of mosque architectural forms in the context of architectural design that continues to evolve. In line with these issues, this study analyzes the concepts of needs and wants that underlie the design of traditional, and contemporary mosques in West Java. The analysis process is carried out by comparing ideograms that represent the concept of the need for Islamic fiqh-based ritual activities, with typograms that represent the elements of the scope and mosque space in the study cases. Furthermore, the analysis results show that the expression of the architectural form of the mosque in each case study is more influenced by the wants of the pious congregation and the personal wants of the architect.